Death as a Concept for Hegel and Heidegger: Between the Context of Phenomenology of Spirit and Being and Time - Wang, Hongru (Transactions on Social Science, Education and Humanities Research, 2024)
This article analyses the concept of death as presented in Hegel’s Phenomenology of Spirit and Heidegger’s Being and Time. For the introduction of Phenomenology of Spirit, the author explores the interconnectedness of death and life. Additionally, in the section on Self-Consciousness, the author explains the logical process of the relationship between dominance and subservience. It becomes evident that death plays a significant role in shaping life, and it is through this relationship that spirit emerges. In Heidegger’s book, authenticity is a result of death, which holds great importance in Dasein’s life process, as it helps man overcome a state of stagnation in ordinary experiences. This essay aims to clarify the existential states and emotions experienced by Dasein that are closely intertwined with the concept of death. Below, three sections will be presented: Cognition of death, Emotions related to death, and the Authenticity that Dasein achieves through confronting death. This essay aims to offer a comprehensive perspective on the significant impact of death on the fundamental nature of life, as well as the strong correlation between death and life as discussed in the works of Hegel and Heidegger. The article seeks to contribute to the ongoing discussion on the existential importance of death in these two philosophical progresses.